Detecting amyloid and tau pathology in Parkinson’s disease, 4R-tauopathies and control subjects with plasma pTau217 - Musso, Giulia; Fiorenzato, Eleonora; Misenti, Valentina; Cauzzo, Simone; Biundo, Roberta; Fogliano, Carmelo A.; Bonato, Giulia; Meissner, Wassilios G.; Campagnolo, Marta; Carecchio, Miryam; Vianello, Francesca; Guerra, Andrea; et al. (Frontiers in Neurology, 2025)
IntroductionPlasma phospho-tau 217 (pTau217) is a biomarker for Alzheimer’s disease (AD) pathology, reflecting amyloid (Aβ) and tau burden, but its role in Parkinson disease (PD) and 4-repeat(4R)-tauopathies remains incompletely understood. We measured plasma pTau217 across the cognitive spectrum of Lewy body diseases (PD, Dementia with Lewy bodies [DLB]) and in 4R-tauopathies, comparing these groups to cognitively unimpaired (CU) and mild cognitive impairment (MCI) individuals.MethodsParticipants included 18 cognitively normal PD (PD-NC), 32 PD with MCI, and 7 PD with dementia (PDD), alongside 4 DLB patients, grouped as PDD/DLB. The 4R-tauopathy group included 28 Progressive Supranuclear Palsy (PSP) and 4 corticobasal syndrome (CBS) patients, compared to 51 CU and 26 MCI individuals. Ptau217 was measured using the fully automated Lumipulse platform, with values adjusted for creatinine levels. Further, the presence of AD-pathology was defined using a validated cut-off based on Aβ-PET.ResultsPTau217 levels were significantly lower in PD-NC and CU individuals compared to those with greater cognitive impairment (PD-MCI, PDD/DLB, and PSP/CBS), and MCI individuals. AD co-pathology was identified in 28% of PDD/DLB and PSP/CBS patients, 16% of PD-MCI, and none of PD-NC. MCI showed the highest pTau217 positivity (35%), while 8% of CU individuals were positive despite normal cognition. In PD, pTau217 negatively correlated with cognitive performance, as assessed by Montreal Cognitive Assessment (MoCA: rs = −0.38, p = 0.004) and Mini-Mental State Examination (MMSE: rs = −0.37, p = 0.006).DiscussionPlasma pTau217 levels serve as a scalable, non-invasive marker of AD-pathology across Lewy body diseases, PSP/CBS, and MCI/CU populations. AD co-pathology independently contributes to cognitive deficits in PD, but not in PSP/CBS.